Over-expression of UDP-glycosyltransferase UGT353G2 confers resistance to neonicotinoids in whitefly (Bemisia tabaci) - Tian-hua Du; Cheng Yin; Lian-you Gui; Jin-jin Liang; Shao-nan Liu; Bu-li Fu; Chao He; Jing Yang; Xue-gao Wei; Pei-pan Gong; Ming-jiao Huang; Hu Xue; et al. (Pesticide Biochemistry and Physiology, 2023)

Climatic aridification restrained late Cenozoic denudation of the Tian Shan in the inland of Asia - Yutong Jiang; Honghua Lu; Ruohong Jiao; Lichen Pang; Rong Yang; Menghan Wu; Xiangmin Zheng; Youli Li (Global and Planetary Change, 2023)

Hydrogeochemical characterization and precursor anomalies of hot springs in the North Tianshan orogen - Zhihua Ding; Xiaocheng Zhou; Chengguo Wang; Jingchao Li; Miao He; Jiao Tian; Kayimu Saimaiernaji; Chengying Zhu; Wei Yan; Rong Ma; Xinyong Li; Na Li; et al. (Applied Geochemistry, 2023)

Effect of iron-loaded sludge biochar amendments on phytoremediation potential of Cr-contaminated soils by Leersia hexandra swartz - Jin-Chao Wang; Ji-Rong Zhao; Qing-Xia Huang; Li-Jiao Yang; Guo Yu; Yu-Feng Xu; Li-Heng Liu (Chemosphere, 2023)

Detecting endosperm cracks in soaked maize using μCT technology and R-YOLOv7-tiny - Yitao Jiao; Zheng Wang; Yuying Shang; Rong Li; Zhixin Hua; Huaibo Song (Computers and Electronics in Agriculture, 2023)

Soil core microbiota drive community resistance to mercury stress and maintain functional stability - Shuai Du; Xin-Qi Li; Jiao Feng; Qiaoyun Huang; Yu-Rong Liu (Science of The Total Environment, 2023)

Novel_miR-1517 mediates CYP6CM1 to regulate imidacloprid resistance in Bemisia tabaci (Hemiptera: Gennadius) - Pei-Pan Gong; Xue-Gao Wei; Shao-Nan Liu; Jing Yang; Bu-Li Fu; Jin-Jin Liang; Ming-Jiao Huang; Tian-Hua Du; Cheng Yin; Yao Ji; Chao He; Jin-Yu Hu; et al. (Pesticide Biochemistry and Physiology, 2023)

High-resolution forest age mapping based on forest height maps derived from GEDI and ICESat-2 space-borne lidar data - Xudong Lin; Rong Shang; Jing M. Chen; Guoshuai Zhao; Xiaoping Zhang; Yiping Huang; Guirui Yu; Nianpeng He; Li Xu; Wenzhe Jiao (Agricultural and Forest Meteorology, 2023)

Ultra-stable, sensitive and broadband photodetector based on large-area 2D bismuth oxyselenide film for multiband image sensing - Shuai Ren; Shiyong Gao; Ping Rong; Lin Li; Mingyi Zhang; Huiqing Lu; Jun Yan; Duoduo Ling; Shujie Jiao; Jinzhong Wang (Chemical Engineering Journal, 2023)

The spatial distribution, health risk, and cytotoxicity of metal(loid)s in contaminated field soils: The role of Cd in human gastric cells damage - Jiao-Yang Ma; Wei-Yu Li; Zi-Yue Yang; Jin-Zhou Su; Li Li; Yi-Rong Deng; Yun-Fei Tuo; You-Ya Niu; Ping Xiang (Science of The Total Environment, 2023)

Amendments of nitrogen and sulfur mitigate carbon-promoting effect on microbial mercury methylation in paddy soils - Yunyun Li; Shu-Shen Dai; Jiating Zhao; Zhi-Cheng Hu; Qin Liu; Jiao Feng; Qiaoyun Huang; Yuxi Gao; Yu-Rong Liu (Journal of Hazardous Materials, 2023)

Anti-inflammatory flavonoid derivatives from the heartwood of Dalbergia odorifera T. Chen - Ni-li Zan; Zi-Han Lu; Xin-Yu Wang; Rong-Ye Wang; Nai-Yun Liang; Hui-Xia Huo; Yun-Fang Zhao; Yue-Lin Song; Peng-Fei Tu; Jiao Zheng; Jun Li (Natural Product Research, 2023)

E3D: An efficient 3D CNN for the recognition of dairy cow's basic motion behavior - Yunfei Wang; Rong Li; Zheng Wang; Zhixin Hua; Yitao Jiao; Yuanchao Duan; Huaibo Song (Computers and Electronics in Agriculture, 2023)

An in silico and in vitro integrated analysis method to reveal the curative mechanisms and pharmacodynamic substances of Bufei granule on chronic obstructive pulmonary disease - Yuan-yuan Ma; Rong Li; Zhi-xian Shang; Wei Liu; Xin-yi Jiao; Liu-yi Liang; Rui Liu; Zheng Li (Molecular Diversity, 2023)

DNA Methylation Alterations and Their Association with High Temperature Tolerance in Rice Anthesis - Bo Li; Haiya Cai; Ke Liu; Bingzhuang An; Rong Wang; Fang Yang; Changli Zeng; Chunhai Jiao; Yanhao Xu (Journal of Plant Growth Regulation, 2023)
DNA methylation is an important epigenetic mechanism involved in gene regulation under environmental stresses in plants. However, little information is available regarding its responses to high temperature (HT) and association with HT tolerance in rice. In this study, fourteen rice genotypes were classified into the susceptible, moderate, and tolerant groups by the high temperature susceptibility index (HTSI) after HT treatment. The changes of DNA methylation in rice anthesis under normal and HT30 conditions were investigated using methylation-sensitive amplified polymorphism31 (MSAP). The MSAP results showed that the DNA methylation level significantly increased in the susceptible rice group and decreased in the tolerant rice group under HT treatment, while no significant difference was observed in the moderate rice group. More hypomethylation events were detected in the tolerant rice group, while more hypermethylation was detected in the susceptible rice group. Forty-four differentially methylated epiloci (DME) were generated under both control and HT conditions, which can clearly distinguish the susceptible, moderate, and tolerant genotypes via PCoA analysis. Approximately 43.18% of DMEs were determined to be tolerance-associated epiloci (TAEs). 63.15% TAEs were sequenced and annotated into 12 genes. Quantitative RT-PCR analysis showed that 12 TAE genes were mainly upregulated in 14 rice genotypes, and their expression levels were related to the HT tolerance of rice. Here, DEGs, generated from a number of genotypes, indicate higher probabilities for association with stress tolerance. Overall, these results suggest that DNA methylation regulation might play a key role in adaptation to HT stress in rice.

Molecular diffusion and pore-scale mechanical dispersion controls on time-variant travel time distribution in hillslope aquifers - Rong Mao; Xin Luo; Jiu Jimmy Jiao; Hailong Li (Journal of Hydrology, 2023)

Discovery of a fossil dwarf antelope outside of Africa and its implications for the late Miocene ecosystem in the northeast margin of the Tibetan Plateau - Shi-Qi Wang; Jimin Sun; Chunxiao Li; Shi-Jie Li; Jiao Fu; Qigao Jiangzuo; Luda Xing; Rong Yang (Gondwana Research, 2023)